Poverty and Its Mitigation Efforts in Aceh Province during the 2020–2024 Period - Zainuddin, Zainuddin; T. Makmur (Indonesian Journal Economic Review (IJER), 2025)
The aim of this study is to provide information on the presence of the poor population in Aceh Province and to evaluate whether the poverty alleviation programs implemented by the Aceh government have had an impact on reducing poverty rates in the province. This research adopts a descriptive qualitative approach, collecting data through observation from the official websites of the government and the Aceh Provincial Statistics Agency concerning the number of poor people and poverty alleviation programs. During the observation period, it was found that there was a significant increase in the number of poor people from 2020 to 2021, which rose by 19,330 individuals, resulting in a total of 834,240 poor people in 2021, or 15.33% of the total population of Aceh Province. However, a significant decline occurred from 2021 to 2022, with a reduction of 27,420 individuals, bringing the number of poor people in 2022 to 806,820. This indicates the success of the poverty alleviation programs, both from the central government and the local government. Nevertheless, the decrease in poverty slowed down considerably from 2022 to 2023, with a mere reduction of 70 individuals, suggesting that the poverty alleviation efforts were less successful, leaving the total number of poor people in 2023 at 806,750. Furthermore, between 2023 and 2024, there was a more substantial decrease in poverty, with a reduction of 2,220 individuals, bringing the total number of poor people to 804,530 by 2024. Therefore, it can be concluded that poverty alleviation in Aceh Province from 2021 to 2022 was relatively successful, from 2022 to 2023 was unsuccessful, and from 2023 to 2024 showed improvement. However, overall, poverty alleviation has not been effective, as the poverty rate in 2024 remains at 14.23% of the total population. Ideally, the poverty rate should be below 8%. Therefore, it is crucial for stakeholders in Aceh Province to design effective and efficient poverty alleviation programs to achieve an ideal poverty rate of ≤ 8% of the total population.